Philosophy of environmental consciousness in the context of digitalization - Tytar, Olena; Bulgakova, Oksana (Вісник гуманітарних наук, 2025)
The article proposes a philosophical reconstruction of the concept of ecological consciousness in the context of the development of digital culture, when ecological ideas, affects and norms are increasingly formed through platforms and algorithmic modes of visibility. The aim is to analyze the philosophical dimensions of ecological consciousness in the context of digitalization and structural transformations of ecological subjectivity. Methods. An interdisciplinary approach was applied, combining social philosophy, ethics, philosophical anthropology and sociology. Results. The results of the study established that modern ecological consciousness is a synthetic phenomenon, where the ethical and value dimensions of responsibility and care and the media-cultural mechanisms of constructing attention, trust and solidarity intersect. The political and economic conditions of «digital capitalism» were not left out of the study, which are capable of both stimulating a «green transition» to a higher level of ecological consciousness and producing «green» symbolic noise. It is argued that the materiality of digital infrastructure (data center energy, ICT carbon footprint) is significant for environmental consciousness, which introduces a new type of «opaque»environmental externalities into ethics. Conclusions. Environmental consciousness in the context of digital culture is not simply the dissemination of environmental information online, but a structural transformation of environmental subjectivity. A conceptual model of «platformed environmental consciousness» is proposed, which describes how digital environments transform environmental subjectivity through three interconnected axes: epistemic within knowledge and misinformation, emotional-affective within emotional moods of anxiety and hope, practical from individual habits to consumption practices and conscious collective action. The need for a double critique within post-nonclassical philosophy is emphasized, both a critique of the «greening» of the digital as a symbolic gesture without material responsibility, and a critique of the «techno-solution» without ethical and civic legitimacy. It is proven that modern ecological consciousness should be simultaneously ethical, media-critical and infrastructural-realistic.